PANDANGAN HAKIM MERANGKAP PEMBUKTIAN DAN PUTUSAN PENGADILAN DALAM SATU WAKTU SIDANG (Studi di Pengadilan Agama Mojokerto) - Afrohatul Laili (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
The main purpose of the study is comprehensively understanding the panel of judges in executing the case investigation process by joining two stages between evidence and court decisions and the views of other judges related to the case. The informants of this research are the judges of the Mojokerto Religious Court. This type of research is empirical research with descriptive data acquisition, while the approach used is qualitative approach. Most of the data are primary data which are obtained/collected from the informants, the judges of Mojokerto Religious Court directly. The analysing the result of the study using descriptive qualitative analysis method. Based on the result of the study, the majority of Religious Court judges of Mojokerto allows the process of case investigation using the merger of two phases, because this merger is not incompatible to the law of procedural law. Therefore, there is no sanction for the judges who apply the process of two phases merging. Moreover, another consideration is to be more efficient both the time and the cost during the process in the court. This opinion is also based on the principle of simplicity, rapidity and low cost. However, one of the judges argued that although the process of merging these two phases does not break the law but the merger should not be done on the grounds that the judge who hadles the case may more understand the subject matter and possible to give the final answer in the form of fair verdict.